2015
DOI: 10.1021/acs.joc.5b01922
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Amides from Imines via Cyanide-Mediated Metal-Free Aerobic Oxidation

Abstract: A new protocol for the direct formation of amides from imines derived from aromatic aldehydes via metal-free aerobic oxidation in the presence of cyanide is described. This protocol was applicable to various aldimines, and the desired amides were obtained in moderate to good yields. Mechanistic studies suggested that this aerobic oxidative amidation might proceed via the addition of cyanide to imines followed by proton transfer from carbon to nitrogen in the original imines, leading to carbanions of α-amino ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…On the basis of our findings7 in conjunction with the previous reports8–10 on the facile generation of umpolung of aldimines with cyanide, we hypothesized that 2‐arylindole‐3‐acetic acid derivatives 4 could be prepared from aldimines 5 obtained from 2‐aminocinnamic acid derivatives 1 and aromatic aldehydes in the presence of a catalytic amount of cyanide, rather than from the corresponding Strecker products 2 in the presence of a stoichiometric amount of a strong base, although the Opatz group reported that cyclization of aldimines 5 with a catalytic amount of cyanide was unsuccessful 4. As demonstrated in Scheme b, the reaction of aldimines 5 with cyanide would afford cyanide adducts II , and the subsequent tautomerization of the resulting cyanide adducts generates anions I 7–10. The resulting anions I would follow the same transformation as shown in Scheme a, leading to the desired indole derivatives 4 .…”
Section: Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…On the basis of our findings7 in conjunction with the previous reports8–10 on the facile generation of umpolung of aldimines with cyanide, we hypothesized that 2‐arylindole‐3‐acetic acid derivatives 4 could be prepared from aldimines 5 obtained from 2‐aminocinnamic acid derivatives 1 and aromatic aldehydes in the presence of a catalytic amount of cyanide, rather than from the corresponding Strecker products 2 in the presence of a stoichiometric amount of a strong base, although the Opatz group reported that cyclization of aldimines 5 with a catalytic amount of cyanide was unsuccessful 4. As demonstrated in Scheme b, the reaction of aldimines 5 with cyanide would afford cyanide adducts II , and the subsequent tautomerization of the resulting cyanide adducts generates anions I 7–10. The resulting anions I would follow the same transformation as shown in Scheme a, leading to the desired indole derivatives 4 .…”
Section: Methodssupporting
confidence: 52%
“…Very recently, we reported a protocol for the synthesis of amides from aldimines via cyanide‐mediated metal‐free aerobic oxidation 7. The mechanistic studies indicated that amides would be formed from aldimines in the presence of cyanide through the following sequences: (i) the addition of cyanide to aldimines to form cyanide adducts II , (ii) a proton transfer from the carbon atom to the nitrogen atom in the resulting cyanide adducts II generating umpolung I , and (iii) subsequent reaction of I with molecular oxygen affording the desired amides.…”
Section: Methodsmentioning
confidence: 99%
“…All solvents were removed to yield the corresponding amide as a white solid. Analytical data of these compounds are in agreement with those reported …”
Section: Methodsmentioning
confidence: 99%
“…The reaction was heated at reflux for 48 h. After cooling to room temperature, the solids were removed by filtration and washed with THF (50 mL). [37,38] General procedure I: Formation of pyridinium salts (6 a-c, 10 a,b, and 14 a) N-(Pyridin-4-yl)benzamide, 9a,b or 13 a (2.0 mmol) was dissolved in MeCN (15 mL) in ap ressure tube. All solvents were removed to yield the corre- Figure 9.…”
Section: Electrochemistrymentioning
confidence: 99%
“…In the presence of Kraft lignin, the milling process instead afforded the N -benzylphthalimide ( 5a ) (33%). The formation of 5a can be explained as a result of a cyanide-catalyzed oxidative amidation of the isoindolinone 6a under the aerobic reaction conditions (ambient atmosphere) present in the ball mill ( Scheme 2 ) [ 27 , 28 , 29 ]. Next, the same reaction was repeated, but this time Zn(OTf) 2 (10 mol%) was added in addition to Kraft lignin in the milling vessel.…”
Section: Resultsmentioning
confidence: 99%